1998
DOI: 10.1055/s-0037-1615197
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mutations in the Canine von Willebrand Factor Gene Associated with Type III von Willebrand Disease

Abstract: SummaryIn humans, type III von Willebrand disease is caused by deletions or nonsense mutations. In dogs, the underlying genetic defects have not been determined yet. We searched for the genetic defect in four related type III deficient Dutch Kooiker dogs obtained from one breeder. Mutation analysis was performed with total RNA isolated from platelets or whole blood. The complete coding region of the vWf gene was amplified by RT-PCR and sequenced by the cycle sequencing technique. Two homozygous mutations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 25 publications
2
26
0
3
Order By: Relevance
“…After sequence analysis of this PCR product, we detected a homozygous mutation (IVS16ϩ1G→A; TGg→TGA) at the splice donor site of intron 16 of the vWF gene. This finding is consistent with that of Rieger et al 9 The mutation changes the reading frame in such a way that the newly formed codon at the normal splice junction is changed to a stop codon at amino acid position 729 in the propeptide. With such a radical mutation, the total absence of vWf:Ag in homozygously affected Kooiker dogs is readily explained.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…After sequence analysis of this PCR product, we detected a homozygous mutation (IVS16ϩ1G→A; TGg→TGA) at the splice donor site of intron 16 of the vWF gene. This finding is consistent with that of Rieger et al 9 The mutation changes the reading frame in such a way that the newly formed codon at the normal splice junction is changed to a stop codon at amino acid position 729 in the propeptide. With such a radical mutation, the total absence of vWf:Ag in homozygously affected Kooiker dogs is readily explained.…”
Section: Discussionsupporting
confidence: 92%
“…A 501-bp fragment generated by primers DKD2 and DKD3 from another region of the cDNA was of the same size in both dogs (data not shown). Sequence analysis of the longer PCR products identified a splice site mutation (IVS16ϩ1G→A; TGgtaa→TGATAA) involving the 1st nucleotide of intron 16 (indicated in bold), resulting in the presence of 46-bp intronic DNA in the mature mRNA (data not shown), as has also been described by Rieger et al 9 The mutation changes the codon at the original splice junction (TGC) into a nonsense stop codon (TGA). This is predicted to terminate the translation process at amino acid position 729.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…15 Here, genomic DNA was isolated from the blood cells of the 4 VWD dogs, and genotyping revealed that all 4 dogs carried a homozygous point mutation (GϾA transition) at the first position of the donor splice site sequence of intron 16, resulting in a stop codon in the propeptide of VWF and thus identifying them as type 3 VWD dogs. 16 All animal experiments were performed in accordance with protocols approved by the Institutional Animal Care and Use Committee of the Catholic University of Leuven (Belgium).…”
Section: Animalsmentioning
confidence: 99%